2012
DOI: 10.1681/asn.2010121253
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Bone Quality in Low- and High-Turnover Renal Osteodystrophy

Abstract: Abnormal bone turnover is common in CKD, but its effects on bone quality remain unclear. We qualitatively screened iliac crest bone specimens from patients on dialysis to identify those patients with low (n=18) or high (n=17) bone turnover. In addition, we obtained control bone specimens from 12 healthy volunteers with normal kidney function. In the patient and control specimens, Fourier transform infrared spectroscopy and nanoindentation quantified the material and mechanical properties of the specimens, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 46 publications
4
91
0
Order By: Relevance
“…Therefore, the relationship between high iPTH and VC cannot be confirmed, but it indicates that lower iPTH is also prone to VC. This result is consistent with recent studies: both high iPTH and low iPTH levels may cause VC [23,24]. A study by London et al [25] showed that HD patients with VC had lower iPTH levels than patients without VC.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the relationship between high iPTH and VC cannot be confirmed, but it indicates that lower iPTH is also prone to VC. This result is consistent with recent studies: both high iPTH and low iPTH levels may cause VC [23,24]. A study by London et al [25] showed that HD patients with VC had lower iPTH levels than patients without VC.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study evaluated bone quality as assessed by material and mechanical properties. The primary finding was that "bone with low turnover had microstructural abnormalities such as lower cancellous bone volume and reduced trabecular thickness" (18). We did not have access to tests, such as bone alkaline phosphatase, vitamin D levels, or fibroblast growth factor-23, that might have provided information on bone health.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, bone surface, connectivity density, cortical thickness, and cortical porosity were better preserved in bone biopsies assessed both by mCT and classic histomorphometry versus renal transplant patients receiving potassium chloride as a control treatment. These architectural parameters have been shown to correlate with biochemical bone properties and thus are likely to be relevant for bone quality (30). In addition, serological biomarkers did not change in the potassium citrate group but decreased significantly in patients taking potassium chloride, indicating better maintenance of bone turnover by citrate administration.…”
Section: Discussionmentioning
confidence: 92%